The construction industry as agents of energy demand configuration in the existing housing stock. (December 2020) - Killip, Gavin; Owen, Alice
Highlights: Construction firms are agents of energy policy. Elements of disruption and continuity are needed for retrofit delivery. Co-ordination, skills, practice innovations, regulation and compliance are key. Energy policy support should be extended to skill and network development. Energy policy and industrial strategy need to be aligned.